10.3% Efficient Green Cd‐Free Cu2ZnSnS4 Solar Cells Enabled by Liquid‐Phase Promoted Grain Growth. Issue 50 (1st November 2022) - Yuan, Xiaojie; Li, Jianjun; Huang, Jialiang; Yan, Chang; Cui, Xin; Sun, Kaiwen; Cong, Jialin; He, Mingrui; Wang, Ao; He, Guojun; Mahboubi Soufiani, Arman; Jiang, Junjie; et al.
Abstract: Small grain size and near‐horizontal grain boundaries are known to be detrimental to the carrier collection efficiency and device performance of pure‐sulfide Cu2 ZnSnS4 (CZTS) solar cells. However, forming large grains spanning the absorber layer while maintaining high electronic quality is challenging particularly for pure sulfide CZTS. Herein, a liquid‐phase‐assisted grain growth (LGG) model that enables the formation of large grains spanning across the CZTS absorber without compromising the electronic quality is demonstrated. By introducing a Ge‐alloyed CZTS nanoparticle layer at the bottom of the sputtered precursor, a Cu‐rich and Sn‐rich liquid phase forms at the high temperature sulfurization stage, which can effectively remove the detrimental near‐horizontal grain boundaries and promote grain growth, thus greatly improving the carrier collection efficiency and reducing nonradiative recombination. The remaining liquid phase layer at the rear interface shows a high work function, acting as an effective hole transport layer. The modified morphology greatly increases the short‐circuit current density and fill factor, enabling 10.3% efficient green Cd‐free CZTS devices. This work unlocks a grain growth mechanism, advancing the morphology control of sulfide‐based kesterite solar cells. Abstract : A liquid‐phase assisted grain growth model for kesterite Cu2 ZnSnS4 (CZTS) is demonstrated via controlled decomposition of a CZTGS nanoparticle layer inserted at the bottom of sputtered precursor. This growth model effectively removes the detrimental horizontal grain boundaries and enlarges the grain size of CZTS, thus significantly improving the carrier collection efficiency and enabling 10.3% efficient Cd‐free CZTS solar cells.